An Epidemiological Study of Nosocomial Infection in Post-Operative Patients.: Pharmaceutical Science-Pharmacy - Sebastian, Robin; Gopalakrishnan, G; Sanil Kumar, P; Prasanth, Lal (International Journal of Life Science and Pharma Research, 2022)
A Nosocomial infection-also called” hospital acquired infection” can be defined as “An infection occurring in a patient in a hospital or other health care facility in whom the infection was not present or incubating at the time of admission.” The term Nosocomial infection is applied to any clinical infection that was neither present nor was in its incubation period, when the patient entered the hospital. Nosocomial infections are one of the most common adverse events during healthcare delivery and a major public health issue affecting morbidity, mortality, and quality of life. At any time, up to 7% of patients in developed and 10% in developing countries will acquire at least one Healthcare-associated infection (HAI), causing a considerable economic burden to the society. It is evident that HAIs result in prolonged hospital stays, long-term disability, increased resistance of microorganisms to antimicrobials, additional cost on health systems, high cost for patients and their family, and preventable deaths. The objective of the study was to find out the morbidity pattern in post-surgical wound infections and suggested measures to minimize exogenous and endogenous sources of Nosocomial infections. Out of total 300 patient's details collected, 98 patients were affected by surgical site nosocomial infection. Staphylococcus aureus is found to be the leading pathogens in post-surgical wound infection. In this study, we also found that reducing preoperative stay can reduce the postoperative surgical site infection. In conclusion, we should clearly understand and identify the nosocomial infections and device a system to track, analyse, monitor prevent and treat. Hospital infection control committee should meet regularly and make recommendations at all levels for prevention of Nosocomial infections. Total prevention may not be possible but can be minimized to significant extent by implementing the guidelines developed during the present study.